Is the pace of japanese mortality decline converging toward international trends? - Wilmoth, J. R.
diagrs.
pp. 593-600
Keywords: Japon; Suecia; Mortalidad; Esperanza de Vida; Calidad de la Vida; Siglo XX; Longevidad